An anthropometric study of craniofacial measurements and their correlation with vertical dimension of occlusion among fully dentate population in Serbia - Živković Nikola; Nikolić Pavle; Kuzmanović-Pfićer Jovana; Perić Mirjana; Milić-Lemić Aleksandra (Stomatološki glasnik Srbije, 2019)
Introduction In clinical conditions vertical dimension of occlusion (VDO) is defined as a distance between the two points, one above and the other one under the mouth, while teeth are intercuspidated. As a result of teeth loss, attrition , abrasion or unsuccessful dental interventions the VDO changes. Decrease of VDO not only changes the esthetic appereance of the lower third of the face, but also affects the function of the orofacial system. The objective of the study was to find correlation of VDO and craniofacial measurements among fully dentate subjects. Material and methods the study was performed at the Clinic of Prosthodontics of University of Belgrade from October 2018 until March 2019. The participants included both genders age range between 22 and 24 years, class I occlusion and intact dentition. Twelve craniofacial lines were measured with specially constructed divider. Gathered results were analyzed in SPSS 22 computer software. Mean values and standard deviation were used for data description. Results the results showed statistically significant correlation in values of some parameters in both genders. The proportion of the face was noticed among all participants, and possibility of analyzing face by thirds. Also the correlation was noticed between the lower facial height and the height of right ear as well as bi-pupillary distance where with increasing distance of bi-pupillary line, the value of the lower facial height was also increased. Statistical significance in values of both genders was noticed in middle facial height (p = 0.006), lower facial height/ vertical dimension of occlusion (p = 0.004), width of nose (p = 0.01), Frankfurt plane (p = 0.008), height of the right ear (p = 0.000). Conclusion Obtained results showed correlation between VDO and craniofacial dimension among young adults with intact dentition.